Mitigating Climate Change Related Floods in Urban Poor Areas: Green Infrastructure Approach - Fahmyddin Araaf Tauhid; Hoferdy Zawani (The Institute for Research and Community Services, Institut Teknologi Bandung, 2018)
Abstract. Natural disasters continue to hit urban areas worldwide, undermining community resilience capacity. The combination of increasing precipitation because of climate change, sea level rise, and uncontrolled rapid urbanization bring greater risk of flooding impacts in urban areas. Such flooding has a disproportionate effect on the urban poor, who often live in informal settlements. Meanwhile, the rapid expansion of informal settlements encroaching on floodplains that restrict the storage of flood waters and the expansion of impermeable urban surfaces also contribute to the increasing magnitude and frequency of flooding. Therefore, it is important to acknowledge the urban poor as the most vulnerable community and also as key party in mitigation efforts. Although mitigation measures are currently in place to lessen the impact of climate change related floods in urban poor areas, little attention has been given to the use of green infrastructure as a mitigation strategy. Hence, this study aimed to examine current practices of green infrastructure (GI) in urban poor areas of Kibera (Kenya), Madurai (India) and Old Fadama (Ghana) to mitigate climate related flood impacts. Using the multiple case study method, it was investigated how urban stakeholders address and overcome the critical issues of governance, finance and awareness to secure the success of GI implementation. It was found that GI requires comprehensive understanding of political, social, economic and environmental aspects of the urban poor population to secure the success of initiatives, while cohesive cooperation and full participation of urban stakeholders is the key. Keywords: Mitigation, climate change, flood, urban poor, green infrastructure.Abstrak. Bencana alam yang melanda wilayah perkotaan di berbagai penjuru dunia berpotensi mengancam kapasitas ketahanan masyarakat. Perpaduan antara peningkatan curah hujan akibat perubahan iklim, kenaikan permukaan air laut, dan pesatnya urbanisasi yang tidak terkendali, membawa risiko banjir yang lebih besar di daerah perkotaan. Ancaman banjir merugikan masyarakat miskin kota yang mayoritas tinggal di permukiman informal. Sementara itu, tumbuhnya permukiman informal secara pesat yang menjangkau wilayah rawan banjir menyebabkan berkurangnya kawasan resapan dan penyimpanan air yang berkontribusi pada peningkatan besaran dan frekuensi banjir. Oleh karena itu, pengakuan terhadap keberadaan kaum miskin kota sebagai komunitas yang paling rentan dan juga aktor kunci dalam upaya mitigasi bencana diperlukan. Meskipun mitigasi bencana saat ini baru dipahami sebagai upaya untuk mengurangi dampak perubahan iklim, khususnya banjir di daerah miskin perkotaan, saat ini perhatian mulai tertuju pada penggunaan infrastruktur hijau sebagai salah satu alternatif strategi mitigasi. Oleh karena itu, penelitian ini bertujuan untuk menguji praktik-praktik infrastruktur hijau di daerah miskin perkotaan di Kibera (Kenya), Madurai (India) dan Old Fadama (Ghana) untuk mengurangi dampak banjir akibat perubahan iklim. Metode multiple case study digunakan untuk menyelidiki bagaimana para pemangku kepentingan menyuarakan dan mengatasi berbagai permasalahan tata pemerintahan, keuangan dan kesadaran untuk mensukseskan penerapan infrastruktur hijau. Sementara itu, keberhasilan penerapan infrastruktur hijau membutuhkan pemahaman yang komprehensif tentang isu-isu politik, sosial, ekonomi dan lingkungan dalam konteks masyarakat miskin kota, disamping kemitraan yang kooperatif dan partisipasi penuh para pemangku kepentingan sebagai kunci utama.Kata kunci: Mitigasi, perubahan iklim, banjir, miskin kota, infrastruktur hijau.Abstract. Natural disasters continue to hit urban areas worldwide, undermining community resilience capacity. The combination of increasing precipitation because of climate change,sea level rise, and uncontrolled rapid urbanization bring greater risk of flooding impacts in urban areas. Such flooding has a disproportionate effect on the urban poor, who often live in informal settlements. Meanwhile, the rapid expansion of informal settlements encroaching on floodplains that restrict the storage of flood waters and the expansion of impermeable urban surfaces also contribute to the increasing magnitude and frequency of flooding. Therefore, it is important to acknowledge the urban poor as the most vulnerable community and also as key party in mitigation efforts. Although mitigation measures are currently in place to lessen the impact of climate change related floods in urban poor areas, little attention has been given to the use of green infrastructure as a mitigation strategy. Hence, this study aimed to examine current practices of green infrastructure (GI) in urban poor areas of Kibera (Kenya), Madurai (India) and Old Fadama (Ghana) to mitigate climate related flood impacts. Using the multiple case study method, it was investigated how urban stakeholdersaddress and overcome the critical issues of governance, finance and awareness to secure the success of GI implementation. It was found that GI requires comprehensive understanding of political, social, economic and environmental aspects of the urban poor population to secure the success of initiatives, while cohesive cooperation and full participation of urban stakeholders is the key. Keywords: Mitigation, climate change, flood, urban poor, green infrastructure. [Diterima: 22 Februari 2018; diterima dalam bentuk akhir: 28 Mei 2018] Abstrak. Bencana alam yang melanda wilayah perkotaan di berbagai penjuru dunia berpotensi mengancam kapasitas ketahanan masyarakat. Perpaduan antara peningkatan curah hujan akibat perubahan iklim, kenaikan permukaan air laut, dan pesatnya urbanisasi yang tidak terkendali, membawa risiko banjir yang lebih besar di daerah perkotaan. Ancaman banjir merugikan masyarakat miskin kota yang mayoritas tinggal di permukiman informal. Sementara itu, tumbuhnya permukiman informal secara pesat yang menjangkau wilayah rawan banjir menyebabkan berkurangnya kawasan resapan dan penyimpanan air yang berkontribusi pada peningkatan besaran dan frekuensi banjir. Oleh karena itu, pengakuan terhadap keberadaan kaum miskin kota sebagai komunitas yang paling rentan dan juga aktor kunci dalam upaya mitigasi bencana diperlukan. Meskipun mitigasi bencana saat ini baru dipahami sebagai upaya untuk mengurangi dampak perubahan iklim, khususnya banjir di daerah miskin perkotaan, saat ini perhatian mulai tertuju pada penggunaan infrastruktur hijau sebagai salah satu alternatif strategi mitigasi. Oleh karena itu, penelitian ini bertujuan untuk menguji praktik-praktik infrastruktur hijau di daerah miskin perkotaan di Kibera (Kenya), Madurai (India) dan Old Fadama (Ghana) untuk mengurangi dampak banjir akibat perubahan iklim. Metode multiple case study digunakan untuk menyelidiki bagaimana para pemangku kepentingan menyuarakan dan mengatasi berbagai permasalahan tata pemerintahan, keuangan dan kesadaran untuk mensukseskan penerapan infrastruktur hijau. Sementara itu, keberhasilan penerapan infrastruktur hijau membutuhkan pemahaman yang komprehensif tentang isu-isu politik, sosial, ekonomi dan lingkungan dalam konteks masyarakat miskin kota, disamping kemitraan yang kooperatif dan partisipasi penuh para pemangku kepentingan sebagai kunci utama.Kata kunci: Mitigasi, perubahan iklim, banjir, miskin kota, infrastruktur hijau.